2020
DOI: 10.1017/s095026882000148x
|View full text |Cite
|
Sign up to set email alerts
|

Role of pulsed-xenon ultraviolet light in reducing healthcare-associated infections: a systematic review and meta-analysis

Abstract: Pulsed-xenon-ultraviolet light (PX-UVL) is increasingly used as a supplemental disinfection method in healthcare settings. We undertook a systematic search of the literature through several databases and conducted a meta-analysis to evaluate the efficacy of PX-UVL in reducing healthcare-associated infections. Eleven studies were included in the systematic review and nine in the meta-analysis. Pooled analysis of seven studies with before-after data indicated a statistically significant reduction of Clostridium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Moreover, due to the variability in the included methodologies of included articles and the variability in the available information for specific WRD types and micro-organisms, firm conclusions regarding the differences of in situ efficacy of the four systems may not be drawn. The observation that all WRD systems lead to a reduction in both environmental outcomes as clinical outcomes is coherent with those made in other reviews [109][110][111][112].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, due to the variability in the included methodologies of included articles and the variability in the available information for specific WRD types and micro-organisms, firm conclusions regarding the differences of in situ efficacy of the four systems may not be drawn. The observation that all WRD systems lead to a reduction in both environmental outcomes as clinical outcomes is coherent with those made in other reviews [109][110][111][112].…”
Section: Discussionsupporting
confidence: 85%
“…A recent systematic review suggested that the use of PX-UV disinfection in addition to the standard disinfection procedures may help reduce the incidence of CDI and MRSA, but not of vancomycin-resistant Enterococci spp (VRE) infection. 11 However, there are a limited number of reports on the clinical effect of PX-UV disinfection, and the findings of the previous studies are inconsistent. 11 A multicenter, randomized controlled study could not show that using a cleaning protocol that combined standard terminal chemical cleaning with the use of a UV device in high-risk rooms occupied by the patients harboring multidrug-resistant organisms and C difficile significantly decreased the risk of MRSA acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, there are a limited number of reports on the clinical effect of PX-UV disinfection, and the findings of the previous studies are inconsistent. 11 A multicenter, randomized controlled study could not show that using a cleaning protocol that combined standard terminal chemical cleaning with the use of a UV device in high-risk rooms occupied by the patients harboring multidrug-resistant organisms and C difficile significantly decreased the risk of MRSA acquisition. 16 In addition, combining UV-based disinfection with standard terminal cleaning resulted in a significant reduction in the hospital-wide risk of CDI and VRE acquisition but not of MRSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These short cycles allow for more rooms per day to be disinfected, covering more square footage within a healthcare facility. A meta-analysis of studies on the use of PX-UV for enhanced disinfection showed a significant reduction in the rates of HO-CDI acquisition (incidence rate ratio 0.73; 95% CI 0.57–0.94) [ 16 ]. In many of the included studies, disinfection with PX-UV was intended for all patient rooms on specific targeted units, not only isolation rooms.…”
Section: Introductionmentioning
confidence: 99%